Система автоматизованого синтезу колійного розвитку залізничних станцій - Малашкін, Вячеслав Віталійович (НТУ «ХПІ», Харків, 2015)
UKR: Процес розробки конструкції колійного розвитку залізничних станцій та вузлів супроводжується масовими і трудомісткими розрахунками з’єднань колій і координат основних точок плану. Значне поліпшення даного процесу досягається за рахунок використання структурно-параметричних моделей станцій у сукупності з методами автоматизованого синтезу станцій. В статті розглядаються моделі та алгоритми графічного формування вхідної моделі станції у середовищі AutoCAD, що значно скорочує тривалість процесу проектування її плану.

RUS: Процесс разработки конструкции путевого развития железнодорожных станций и узлов сопровождается массовыми и трудоемкими расчетами соединений путей и координат основных точек плана. Значительное улучшение данного процесса достигается за счет использования структурно-параметрических моделей станций в совокупности с методами автоматизированного синтеза станций. В статье рассматриваются модели и алгоритмы графического формирования входной модели станции в среде AutoCAD, значительно сокращающие продолжительность процесса проектирования ее плана.

ENG: The process of design gridiron railway stations and units accompanied by massive and time-consuming calculations compounds ways and coordinates the main points of the plan. Significant improvement of this process is achieved through the use of structural and parametric models (input, internal and output models) stations in conjunction with the automated synthesis methods stations. In this formalization scheme gridiron station is based on a directed graph. The Aim. Preparing data input model in the form of lists of characteristic points of the incidence scheme takes considerable time. In this context, the task of developing models and algorithms for interactive graphical form input model of the plant. Methods of solution. To solve the problem using the methods of graph theory and analytic geometry. The Results. To provide interactive input and editing schemes station designed structure of the input model gridiron based on digraph algorithms build and conversion to the internal model to automatically calculate the coordinates of the station plan. The proposed models and algorithms used in the development of a graphical editor-aided design of railway stations on the basis of AutoCAD. Conclusions. Using a graphical editor for automated plant design reduces overall costs up to 60%.
Система автоматизированного синтеза путевого развития железнодорожных станций
System for Automated Synthesis of Track Development Railway Stations
В. Малашкін: ORCID 0000-0002-5650-1571
Keywords: залізнична станція; колійний розвиток; орієнтований граф; синтез; железнодорожная станция; путевое развитие; ориентированный граф; railway station; gridiron; directed graph; synthesis; AutoCAD; КСВ